Air Quality and Microclimatic Parameters During Excavation of Mala Kapela Tunnel (Rudarsko-geološko-naftni zbornik, 2022)
During excavation of the Mala Kapela tunnel, measurements of harmful gases concentration, ventilation parameters and microclimatic parameters were performed. Measurements were done in 17 occasions during period of 16 months, along the advance of the tunnel excavation. Consequently, large amount of data was obtained, in different tunnel chainages, ventilation ducts length, and in different work operations during the excavation.Main sources of harmful gases during tunnel excavation are explosives and diesel equipment. The concentration of the same mainly depends on explosive charge and overall diesel equipment power, present at the excavation face of the tunnel. Continuous measurements of the concentration of carbon monoxide (CO) and dioxide (CO2), and nitrogen oxide (NO) and dioxide (NO2) was performed during drilling, blasting, and loading and haulage operations. Measurements were done in 45 cases in total. Recorded data was analysed, where peak concentrations were joined to corresponding operation and the tunnel chainage. Regulations on threshold limit values were used to determine if concentrations rise above the permissible ones. In case they do, the time required for dilution of gases below permissible concentration was noted. Typically, concentrations of all measured gases rise rapidly after blasting. Afterwards, ventilation system acts to dilute them and maintain them relatively constant until the end of loading and haulage. According to measurements in this research, highest concentrations and longest time of dilution were found after blasting. At the same time, concentration of all measured gases exceeds permissible values. Carbon monoxide is found to exceed permissible values during all work operations. It shows most frequent transgression above the limit (in 33 to 100% of cases) and highest time of dilution (up to 40 min).Air supply to the excavation face was measured in 25 cases. It was correlated to the length of ventilation ducts, as the tunnel excavation advances. Results show the trend of air flow drop of 0,3 to 1,2 m3/s per 100m of duct length, with average value of 0,7 m3/s. In accordance with air flow drop, higher peak concentrations and longer time of dilution was observed for drilling and blasting operations. Conversely, lower concentrations and shorter time of dilution were found for loading and haulage operation. This could be attributed to longer truck cycle as excavation advances, thus less diesel units are present in proximity of the excavation face.Measured data on microclimatic parameters was correlated to season changes, distance form tunnel entrance and mutually. Air temperature was measured in 8 cases, along the tunnel and outside in the proximity of the entrance. Recorded data shows that temperature is constant along the tunnel. That is, there is no change with depth of the tunnel below surface, which is up to 433m. It was found that temperature mainly depends upon season and upon outer air that is supplied by ventilation to the tunnel. Highest temperature was recorded during summer (20 to 27 °C), when inner and other temperature are in approximate equilibrium. Lowest inner temperature was recorded during winter (12 to 17 °C), when difference from outer temperature rises.Relative humidity was measured in 14 cases. Recorded data shows random character, so no relations were derived, except that inner air is more humid on average and it's humidity varies much less compared to the outer air. Outer humidity ranges between 36 and 99%. Inner humidity ranges between 53,6 and 99,3 %, and it was 11,8% higher on average. Air pressure was measured in 15 cases. It was found that it corresponds to the outer atmospheric pressure. There is normal pressure drop with distance from tunnel entrance, as vertical alignment of the tunnel changes it's altitude.